The Effect of Heat Treatments on the Corrosive Behavior of Aluminum-Zinc Alloy - Ibrahim Ahmed, Huwaidah (International Journal of Psychosocial Rehabilitation, 2020)
Included This search a study Feature Corrosion For an alloy,, Aluminum 7020 The container is 4% zinc and 1% magnesium. Treat it Superficially" With rays The laser And compare it By sample From The alloy as such Poured In two ways One of them, immersion samples with a solution saline ingredient of 3.5% NaCl with distilled water, with different periods of time (5, 8, and 15 days), were done and accounted for. Rate corrosion as a way to lose weight and in units (mdd). As for Other, She included account Rate Corrosion using Device polarization And using solution Acidic ingredient From Acid HCL Turns out from the results that rate corrosion, nope, the two methods are being less distant transactions by laser, and that returns to me breadth bezel immortality distance transaction by laser.